The Influences of Wear Debris on the Fretting Wear Behavior of Inconel718 Laser Cladding Alloy Layer - XU Zhibiao, XIE Sen, WANG Xiaoyi, LI Dexiang, LYU Xiaowen (Cailiao Baohu)
Fretting wear is a material damage phenomenon caused by small vibrations between tightly contacting surfaces.Studying the role of debris in fretting wear is of great significance for revealing the damage evolution of materials during fretting wear.In this work， a fretting wear test was conducted on Inconel718 laser cladding alloy layer using ball/plane point contact method on a multifunctional friction and wear testing machine.After the experiment，the mechanical dynamic characteristics during fretting wear process are obtained by analyzing the Ft-D (friction displacement) curve and COF (coefficient of friction) curve.In addition， scanning electron microscopy (SEM) and three-dimensional profilometer (3D) were used to analyze the damage morphology of the contact interface and reveal the main damage mechanism of micro motion wear.The particle size distribution calculation software (Nano Measurer) was employed to statistically analyze the particle size distribution of abrasives.Results showed that the particle size of abrasive debris is mainly distributed between 1～3 μm， and the magnitude of displacement amplitude was positively correlated with the speed of debris discharge.At large displacement amplitudes， the size of the debris was relatively large，which could easily cause abrasive wear， while at small displacement amplitudes， debris was prone to accumulate and hinder the progress of wear.Moreover， under high normal loads， the generation of debris accelerated and exacerbated surface damage to the specimen， with fatigue wear and abrasive wear playing a dominant role.Under small normal loads， debris could reduce the friction force and friction coefficient.In addition， the removal of debris would not change the fretting regime.